Evaluating Drug Safety in Pregnancy: A Hospital-Based Study on TGA Classification and Prescription Practices in Indonesia - Sastranegara, Hawariyyun; Sutrisna, Eman; Nafisah, Nafisah; Priyanto , Edy; Purnawan, Iwan; Ariesto, Mohammad Rizky; Sulistyo, Hidayat (Universitas Andalas, 2025)
Pregnant women are frequently prescribed medications, yet limited data exist on the safety profiles of these drugs in low-resource settings. The Therapeutic Goods Administration (TGA) classification system is a critical tool to evaluate fetal risks, but its application in Indonesian clinical practice remains understudied. This study aimed to analyze prescription patterns and TGA safety categories of drugs prescribed to pregnant women at a tertiary hospital in Indonesia. A cross-sectional study was conducted using medical records of 374 pregnant women at Bunda Arif Hospital (2021-2022). Drugs were classified according to TGA categories (A, B1, B2, B3, C, D, X). Data were analyzed descriptively (frequencies, percentages) and compared across trimesters. Most patients (63%) received one drug, primarily electrolytes/minerals/vitamins (67%). Based on TGA classification, 33% of drugs were Category A (safe), while 27% were Category D (e.g., high-dose Vitamin A). Notably, Category D drugs were increasingly prescribed across trimesters (12% in 1st trimester to 46% in 3rd trimester). No Category X drugs were identified. Conclusion: Despite overall adherence to safe prescribing (Category A), the high prevalence of Category D drugs, particularly Vitamin A, highlights a critical gap in perinatal pharmacovigilance. Clinicians should prioritize evidence-based guidelines to mitigate potential teratogenic risks in pregnancy.